2018
DOI: 10.3390/su10020567
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability, Transformational Leadership, and Social Entrepreneurship

Abstract: This article examines the extent to which culturally endorsed transformational leadership theories (CLTs) and the sustainability of society, both considered societal level institutional indicators, impact the emergence of social entrepreneurship. Using 107,738 individual-level responses from 27 countries for the year 2009 obtained from the Global Entrepreneurship Monitor (GEM) survey, and supplementing with country-level data obtained from Global Leadership and Organizational Behavior Effectiveness (GLOBE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 96 publications
3
83
0
5
Order By: Relevance
“…This research focuses specifically on charismatic and autonomous leadership behaviours, believing that these types are conceptually the most closely related to entrepreneurship (Stephan and Pathak, 2016). Authors such as Coker et al (2017), Gupta et al (2004), Ling et al (2008) and Muralidharan and Pathak (2018) conducted studies in a similar direction, as they provided evidence on the association between leadership (particularly charismatic and autonomous) and entrepreneurship. Although these authors focused their analysis on social and corporate entrepreneurship, this evidence may suggest that entrepreneurs are characterized by these types of values and therefore their outcome can be differentiated in terms of either charisma or autonomy.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This research focuses specifically on charismatic and autonomous leadership behaviours, believing that these types are conceptually the most closely related to entrepreneurship (Stephan and Pathak, 2016). Authors such as Coker et al (2017), Gupta et al (2004), Ling et al (2008) and Muralidharan and Pathak (2018) conducted studies in a similar direction, as they provided evidence on the association between leadership (particularly charismatic and autonomous) and entrepreneurship. Although these authors focused their analysis on social and corporate entrepreneurship, this evidence may suggest that entrepreneurs are characterized by these types of values and therefore their outcome can be differentiated in terms of either charisma or autonomy.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…According to these authors, these kinds of leaders tend to work individually and support low levels of risk and uncertainty: characteristics that ultimately affect entrepreneurial activity. Gupta et al (2004) and Muralidharan and Pathak (2018) also suggested that autonomous leadership might affect entrepreneurial activity negatively, though they excluded this variable from their analysis precisely because of this negative influence and its low explanatory capacity. Coker et al (2017), at the theoretical level, concluded that societies characterized by autonomous leadership tend to decrease the level of entrepreneurial activity oriented towards social purposes.…”
Section: Leadership and Entrepreneurshipmentioning
confidence: 99%
“…According to our results, by understanding the style of thinking we can distinguish sustainable entrepreneurs from other entrepreneurs. Our paper provides preliminary answers to recent calls for a better understanding of the sustainable entrepreneur phenomenon [82,86]. In the Iranian context, survey data from 177 entrepreneurs showed that those entrepreneurs that have other values and that are highly future-oriented have a greater tendency to undertake sustainability-oriented actions [14].…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable entrepreneurship is a new emerging stream of research in the entrepreneurship literature [82][83][84][85][86]. Sustainable entrepreneurs have a high level of environmental and social concern and contribute positively to environmental degradation [87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation